2009
DOI: 10.1186/1472-6920-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices around health research: the perspective of physicians-in-training in Pakistan

Abstract: Background: Health research training is an essential component of medical education and a vital exercise to help develop physician research skills. This study was carried out to assess the level of knowledge, attitudes and practices towards research amongst a group of Post Graduate Medical Trainees (PGMTs') at Aga Khan University (AKU), Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
103
5
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(130 citation statements)
references
References 8 publications
15
103
5
7
Order By: Relevance
“…Published data about residents' attitudes toward research during training in a range of specialties suggest that not all residents are enthusiastic about doing research during residency and that some do not value research as a useful academic exercise [10][11][12][13][14][15][16][17][18][19][20]. This is in contrast to our results, which indicated that the great majority of the participating residents were enthusiastic about research and believed that residents must participate in research.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Published data about residents' attitudes toward research during training in a range of specialties suggest that not all residents are enthusiastic about doing research during residency and that some do not value research as a useful academic exercise [10][11][12][13][14][15][16][17][18][19][20]. This is in contrast to our results, which indicated that the great majority of the participating residents were enthusiastic about research and believed that residents must participate in research.…”
Section: Discussioncontrasting
confidence: 56%
“…Furthermore, 96.8% of ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫العرشين‬ ‫املجلد‬ ‫الثاين‬ ‫العدد‬ those respondents believed that lack of time was a reason behind this. Other influences included lack of availability of mentors (72.7%) and funding (62.8%) [10]. In our study the main perceived barriers to conducing research by residents included lack of research training (93.2%), lack of allocated research time (89.5%), work-related stress (83.2%) and lack of supervisors (73.2%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…8,9 The questionnaire consisted of several parts. The first part pertained to a collection of demographic information of the PGs: Age, gender, specialty, year of postgraduation, and marital status.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…17 However, e-learning packages need to be reinforced by teaching from skilled practitioners, 18 in this case expert prescribers.…”
Section: Education Deliverymentioning
confidence: 99%